SCANNING ELECTRONIC MICROSCOPE EVALUATION OF A TUNISIAN SOIL - MOHAMED ABDELWAHEB; VALENTIN NEDEFF; SONIA DRIDI-DHAOUADI; EMILIAN MOSNEGUTU; ALEXANDRA-DANA CHITIMUS (Journal of Engineering Studies and Research)
This work present a soil analysis by scanning electronic microscope. The soil was collected from Tunisia. The analysis of soil show the highly presence of carbon and oxygen. The carbon is well used to retain heavy metals and pesticide. The soil presents also a high level of lead, this level present a high risk of water resource pollution